A Scientometric Analysis of Studies on Risk Management in Construction Projects - Robert Osei-Kyei; Timur Narbaev; Godslove Ampratwum (Buildings, 2022)
Risk management is one of the topical areas in construction project management research. However, no attempt has been made in the past decades to explore the emerging themes in this area. This paper reviews the research trends in risk management in construction. The bibliometric data of 1635 publications between 1979 and 2022 were extracted from Scopus using a set of keywords. The study used VOSviewer and Gephi to conduct a scientometric analysis on the extracted publications. The review outcome indicates a significant increase in publications on risk management in construction, with about 205 publications recorded between 2021 and 2022 alone. Based on this analysis, it is projected that the next decade will see significant research on risk management, especially as the construction industry moves towards Industry 5.0 with many uncertainties. Further, the most productive countries of risk management studies in construction include China, the United States, the United Kingdom, Australia, and Hong Kong. Emerging key research areas are discussed using network diagrams and clusters. These areas include the processes in risk management, risk analytical models and techniques, sources of risk and uncertainties, effective knowledge-based systems for improved risk management, risk contingency in construction contracts, risk-integrated project planning and scheduling, and stakeholder management. The findings of this study inform researchers on the current progress of risk management studies in construction and highlight possible research directions that can be considered.